Isu Gender Pada Novel Genduk Duku Karya Y.B. Mangunwijaya (Analisis Wacana Kritis) - Feona Pramoda Wardhani; Rhani Febria (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study analyzes gender issues in Genduk Duku, a novel by Y.B. Mangunwijaya, through Michel Foucault’s Critical Discourse Analysis. Set in the historical context of the Mataram Kingdom, the novel portrays various forms of gender inequality experienced by female characters, particularly Genduk Duku, within a patriarchal social structure. This research aims to describe the manifestations of gender issues, power relations, and forms of female resistance depicted in the text. This qualitative descriptive research employs content analysis techniques. The data consist of textual excerpts from the novel that represent subordination, objectification, stigmatization, marginalization, and symbolic violence against women. The analysis is guided by Foucault’s concept of power relations, including power over the social body, power over the sexual body, and power over thought, all of which operate through discourse, cultural institutions, religion, and political structures. The findings show that women in the novel are positioned as objects of male and aristocratic power. The female body is treated as property of the ruler, a sexual commodity, and an element of a social system that demands obedience. Patriarchal discourse spreads through customary rules, royal law, and linguistic constructions that normalize domination. However, the study also reveals various forms of resistance, expressed through the female characters’ courage to reject harassment, defend their dignity, and make autonomous life decisions. These results indicate that Genduk Duku functions not only as a historical narrative but also as a critique of the enduring nature of gender inequality. This research contributes to feminist literary studies and expands the application of Foucault’s theory in examining power relations within Indonesian literary texts.